Effectiveness of an Add-on Intervention Based on Yoga Practice on the Depression' Severity: A Randomized Controlled Trial - Kumari, Nitu; Yadav, Anuradha; Sankhla, Manisha (Medical Research and Its Applications Vol. 11, 2024)
Introduction: Depression contributes significantly to the global health burden. Yoga leverages many physiological and psychological changes involved in mood enhancement and may have the potential to be effective in patients with depression. Yoga comprises a mind-body intervention consisting of various elements including asanas, pranayama, and dhyana. Exercise, meditation, tai-chi, qigong, and yoga have the potential to be effective in many patients with clinical anxiety, emphasizing some physiological and psychological changes that are involved in mood improvement methods. Aim: The present study determines and compares the severity of depression in the study participants (with and without add-on yoga intervention) with 3 months of follow-up and analyse how different domains of depression changed in patients of depression with and without add-on yoga intervention. Materials and Methods: An interventional study was conducted on 60 patients with depression aged 18-45 years, who were randomized into an interventional group (with yoga intervention as an add-on) and a control group (without the intervention of yoga as an add-on). All patients with depression are allowed to continue their medication (conventional treatment) as prescribed by their physicians. Depression scores were measured using the Hamilton Depression Rating Scale (HDRS), at the beginning (baseline), after one month and three months. Results: Out of 60 patients with depression, 39 (65%) were males and 21(35%) females. The interventional group's mean age was 28.23±5.42 years, while the control group's mean age was 30.90±8.54 years with a non-significant difference. The preponderance of the participants were married men from an urban setting with a higher socioeconomic background. While no dominance of education, occupation and family type was observed. A statistically significant difference was observed with time scale at baseline, after one month and three months in both, the interventional group (F (1.543, 44.752) = 408.14, p < 0.001) and in the control group (F (1.720,49.877) = 5.740, p < 0.05). A significant difference was also observed between the interventional and control groups (p < 0.001) after three months of yoga intervention, whereas no significant difference was observed at baseline and after one month of yoga intervention. Repeated measures ANOVA reveals the statistically significant difference among various domains of depression score with a time scale in the interventional group with yoga as an add-on, for Depressed mood, Insomnia (early, middle and late), Work & Activity, Anxiety (psychic and somatic), Somatic symptoms (GI and General) and Loss of weight, whereas no significant difference occurred in other domains. A significant difference was also observed in the control group only for Insomnia (early and middle) and somatic anxiety. Conclusion: Yoga intervention resulted in a significant reduction in depression scores within one month and improved its various domains (Depressed mood, insomnia (early, middle, and late), work and activity, anxiety (psychic & somatic), somatic symptoms (GI & general), and weight loss) significantly, whereas conventional treatment benefits take longer time and only improve “Insomnia (early & middle) and Anxiety-somatic” domains of depression.